An Application of the CCSR Noncognitive Framework: Bringing Together Typical and Exceptional Student Research - Sara E Taylor (Educational Considerations, 2023)
The University of Chicago Consortium on School Research (CCSR) published a report in 2012 entitled Teaching Adolescents to Become Learners. The Role of Noncognitive Factors in Shaping School Performance: A Critical Literature Review in which they drew together research from fields such as psychology, economics, and education to present noncognitive factors as a malleable means to improve student performance in school. According to the framework derived by CCSR, noncognitive factors include academic mindsets, academic perseverance, academic behaviors, learning strategies, and social skills, which interact to influence academic performance. Researchers often focus on either typically developing or exceptional student populations. This division is not reflected in K-12 schools, where teachers have a diverse set of learners in each classroom. This paper draws together research with typically developing or exceptional student populations to align the terminology with the CCSR framework to encourage greater collaboration across disciplines.
Keywords: Noncognitive-factors; students with disabilities; post-secondary transition; noncognitive skills; non-academic skills; social-emotional skills; soft skills